2023
DOI: 10.1111/jvim.16824
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory microbiota and its impact on health and disease in dogs and cats: A One Health perspective

Abstract: Healthy lungs were long thought of as sterile, with presence of bacteria identified by culture representing contamination. Recent advances in metagenomics have refuted this belief by detecting rich, diverse, and complex microbial communities in the healthy lower airways of many species, albeit at low concentrations. Although research has only begun to investigate causality and potential mechanisms, alterations in these microbial communities (known as dysbiosis) have been described in association with inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 149 publications
0
1
0
Order By: Relevance
“…For instance, an increased diversity of intestinal bacteria is associated with a reduced probability of developing conditions such as obesity and enteritis ( Zhu et al., 2022 ; Wang et al, 2023 ). The microbial community reside in the upper respiratory tract exerts colonization resistance, effectively impeding pathogen colonization and thereby reducing the likelihood of lung infection ( Vientós-Plotts et al, 2023 ). The disruption of the upper respiratory microbiota is associated with the pathogenesis of secondary infections that caused by respiratory virus.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an increased diversity of intestinal bacteria is associated with a reduced probability of developing conditions such as obesity and enteritis ( Zhu et al., 2022 ; Wang et al, 2023 ). The microbial community reside in the upper respiratory tract exerts colonization resistance, effectively impeding pathogen colonization and thereby reducing the likelihood of lung infection ( Vientós-Plotts et al, 2023 ). The disruption of the upper respiratory microbiota is associated with the pathogenesis of secondary infections that caused by respiratory virus.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes of the immune system can also travel between mucosal-associated lymphoid tissues, which include the gastrointestinal tract and the respiratory system, through the "common mucosal immune system" (Chase, 2018). As a result, it has been reported that dysbiosis at either site (gastrointestinal tract and respiratory system) can promote inflammation and dysbiosis at the other site (Vientos-Plotts et al, 2023). Mateer et al (2015) took this one step further and reported that the respiratory microbiome is influenced by immigration from the gut through potential aspiration, which may impact the microbiota of the lungs.…”
Section: Introductionmentioning
confidence: 99%